2007
DOI: 10.1002/cncr.23024
|View full text |Cite
|
Sign up to set email alerts
|

Zone‐specific remodeling of tumor blood vessels affects tumor growth

Abstract: BACKGROUND.Chaotic organization, abnormal leakiness, and structural instability are characteristics of tumor vessels. However, morphologic events of vascular remodeling in relation to tumor growth are not sufficiently studied yet.METHODS.By using the rat rhabdomyosarcoma tumor model vascular morphogenesis was studied by light and electron microscopy and immunohistochemistry in relation to tumor regions such as tumor surrounding (TSZ), marginal (TMZ), intermediate (TIZ), and center (TCZ) zones.RESULTS.The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…This is in accordance with the notion that the Ang-1-Tie2 interaction has an inhibitory effect on tumor growth through improved vessel stabilization (42). It has been shown that vascular stabilization per se results in extensive necrosis of tumor tissue (43,44). The decrease of Ang-1 expression in T a compared with normal bladder epithelium as we show here also supports this concept and is probably an important step in bladder carcinogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with the notion that the Ang-1-Tie2 interaction has an inhibitory effect on tumor growth through improved vessel stabilization (42). It has been shown that vascular stabilization per se results in extensive necrosis of tumor tissue (43,44). The decrease of Ang-1 expression in T a compared with normal bladder epithelium as we show here also supports this concept and is probably an important step in bladder carcinogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…While tumor cells organized around the stabilized vessels survive the therapy, tumor tissue areas far from the stabilized vessels become necrotic. Recently, it was demonstrated that blood vessels localized in the central part of tumor become stabilized endogenously by increased integration of SMC or pericytes into the vessel wall and that this process was accompanied by necrosis of tumor tissue (Tilki et al 2007). In line with these Wndings, our current data show for the Wrst time that anti-angiogenic therapy greatly accelerates and extends the process of necrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Especially in the central areas of the tumor blood vessels seem to undergo a partial stabilization, which is associated with a signiWcant reduction in vascular density and an extended necrosis of tumor tissue in these tumor regions (Tilki et al 2007). Recent studies of our group and other groups have shown that a stabilization or a partial "normalization" of the tumor vascular bed to the Wrst is rather harmful than good to the tumor, and secondly, perhaps the eYciency of the previously established therapeutic approaches, such as chemotherapy or radiotherapy could be improved (Ergün et al 2001(Ergün et al , 2006(Ergün et al , 2008Jain 2005;Neskey et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, tumor vessels prove to be functionally inferior. The resulting undirected blood flow with areas of oversupply as well as areas of undersupply complicates an efficient administration of intravenous drugs in cancer therapy (2). However, the vascular network can mature by recruitment of pericytes and smooth muscle cells (SMC) to stabilize the immature tumor vessels and this process is accelerated when anti-angiogenic agents were used (3, 4).…”
Section: Introductionmentioning
confidence: 99%